Development of Tri-N (niteni, nirokke, nambahi) based e-modules on linear equations material for junior high school students - Kusumaningrum, Betty; Istiqomah, Istiqomah; Langobelen, Petrus Damianus Sapan (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
This study was motivated by the need to enhance student understanding of linear equations through innovative and practical learning resources. The primary aim was to develop and evaluate the validity and practicality of a Tri-N-based E-Module specifically designed for linear equation material. Utilizing a research and development (R&D) approach, the study followed the Four-D model, comprising Define, Design, Develop, and Disseminate stages. Conducted at SMP Negeri 3 Yogyakarta, the research involved 26 eighth-grade students as participants, with data collected through interviews and questionnaires, including validation surveys by material experts, media specialists, and students. The resulting E-Module, tailored to the learning needs of eighth-grade students, was validated with high scores from experts in material and media. Student feedback strongly affirmed its practicality and efficacy in facilitating learning. These findings confirm the Tri-N-based E-Module as a valid and practical tool for teaching linear equations, with significant potential to improve learning outcomes and instructional quality in mathematics education.